Voxels: Rapid Assembly of Small Materials Building Blocks (Voxels) into Large Functional 3D Metamaterials (Adv. Funct. Mater. 26/2020). (25th June 2020) - Hahn, Vincent; Kiefer, Pascal; Frenzel, Tobias; Qu, Jingyuan; Blasco, Eva; Barner‐Kowollik, Christopher; Wegener, Martin
Abstract : In article number 1907795, Vincent Hahn and co‐workers manufacture a mechanical metamaterial containing more than one hundred thousand chiral 3D unit cells and more than three hundred billion voxels by using rapid multi‐focus multi‐photon 3D laser printing. This technology uses an array of 3 × 3 laser foci and allows for sub‐micrometer voxel sizes at printing rates of about ten million voxels per second.